THE IMPACT OF SOCIAL MEDIA TOWARDS STUDENTS’ MOTIVATION AND STUDENTS’ ATTITUDE OF LEARNING ENGLISH IN SUMBAWA UNIVERSITY OF TECHNOLOGY - Wirentake, Wirentake (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aimed at investigating the impact of social media towards students’ motivation and students’ attitude of learning English in Sumbawa University of technology. The study was descriptive quantitative. Participants of this study consisted of 120 students of management department, while the instrument used was questionnaire using likert-scale. A quantitative approach was utilized for data collection, while a descriptive analysis method was used to analyze the study. The results of the study showed that social media impact students’ motivation of learning English positively, and students also showed positive attitudes on the use of social media in language learning. It can be concluded that social media might has vital role in language learning beholding to the findings of the study, therefore it is important to encourage students to use social media platforms in language learning. Further study are suggested to investigate specifically on which social media platforms are best to be used in language learning and to see whether or not the study program has any influence on students’ perceptions of using social media in language learning as this study was conducted only in one study program.